A performance evaluation and comparison model for Urban Public Healthcare Service Quality (UrbPubHCServQual) by Fuzzy TOPSIS Method. Issue 3 (27th May 2022) - Khambhati, Rupal; Patel, Hiren; Kumar, Satendra
ABSTRACT: We propose a conceptual performance evaluation and a comparison model to assess public-health-care-service quality in a fuzzy environment using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). First, it aims to explore and validate service-quality measurement constructs for public-health-care services using a Likert scale. Second, the study evaluates and compares service quality for three urban public-health-care facilities from Gujarat, India, using fuzzy linguistic analysis with consideration of feedback from health-care experts. We carried out a two-stage data collection process involving, first, development of a questionnaire and gathering of responses from patients and, second, an advance supplementary questionnaire and collection of feedback from health-care experts for in-patient services. Responses from patients were split into two random samples for Urban Public Healthcare Service Quality (UrbPubHCServQual) scale construction and validation. We derived a six-construct measurement model and used this to development the advanced supplementary questionnaire. The advance supplementary questionnaire was evaluated by 15 health-care experts to enable us to compare the performance of three urban public health-care facilities. The result indicated a six-construct measurement model for evaluating public-health-care-service quality. The measurement model was validated with respect to three aspects: first, the factor loadings of the two samples showed a similar pattern; second, the coefficient alpha analysis brought the same result for two samples; and third, the percentage of variance explained by various constructs was similar in two samples. Applying TOPSIS, the service quality of urban public-health-care facilities was compared and ranked on the basis of proximity to the ideal solution.